Comparison of cultures immediately incubated intraoperatively with cultures incubated postoperatively in the laboratory for causes of periprosthetic loosening [Protez gevşemelerinin etyolojik tanısında ameliyathanede hemen ekilen kültürlerin laboratuvarda ekilenler ile karşılaştırılması] - (:unkn) unknown (Marmara University, 2014)
Objectives: Our study aimed to show whether cultures that are incubated immediately in the operating room (OR) during surgery are superior to those prepared in the laboratory. Patients and Methods: The results of bacteriologic cultures of the specimens processed immediately in the OR during surgery or afterwards in the bacteriology laboratory were compared. Thirty two cases were enrolled in this study. C-reactive protein (CRP) levels and erythrocyte sedimentation rates (ESR) levels were detected preoperatively. Liquid, swab, and tissue biopsy specimens were obtained to be processed separately in the OR or in the bacteriology laboratory. Each specimen was also examined by Gram-staining. Results: Among 32 cases eight were infected. The average level of CRP was significantly higher in the infected group than in the aseptic group (p=0.003). There was no statistical significance for ESR levels between these groups. Of the eight infected patients, only three specimen out of 42 (7.1%) were Gram-positive. For the specimens processed in the operating room the isolation of the bacteria from liquid specimen cultures was found to be significantly higher than the swab, and tissue biopsy cultures (p<0.001). Conclusion: Statistical analysis showed that the isolation of the bacteria from fluid material was statistically significant (p<0.001). Therefore, we conclude that inoculation of fluid material into the blood culture bottles in the OR may increase the chance of yielding organisms. © 2014, Marmara University. All rights reserved.
Keywords: Arthroplasty loosening; Infected loosening; Intraoperative culture; Microbiological diagnosis